Rediscovering Dara Shikoh: A Path to Social Harmony in Contemporary India (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This study revisits the life and works of Dara Shikoh, the 17th-century Mughal prince, to explore his vision for social harmony and its relevance to contemporary India. By examining Dara Shikoh's literary and philosophical contributions, particularly his treatise Majma-ul-Bahrain, this research highlights his efforts to bridge the divide between Hinduism and Islam.Through a critical analysis of Dara Shikoh's works and their historical context, this study demonstrates how his ideas on tolerance, mutual respect, and coexistence can inform strategies for promoting social harmony in India today. By rediscovering Dara Shikoh's legacy, this research aims to contribute to a deeper understanding of India's rich cultural heritage and its potential to foster greater social cohesion.This study's findings have significant implications for scholars, policymakers, and community leaders seeking to promote interfaith dialogue and social harmony in India. By exploring Dara Shikoh's vision for a more inclusive and harmonious society, this research offers a timely and valuable contribution to the ongoing conversation on social cohesion and national integration